Decreased blood vessel density and endothelial cell subset dynamics during ageing of the endocrine system. (20th November 2020) - Chen, Junyu; Lippo, Luciana; Labella, Rossella; Tan, Sin Lih; Marsden, Brian D; Dustin, Michael L; Ramasamy, Saravana K; Kusumbe, Anjali P
Abstract: Age‐associated alterations of the hormone‐secreting endocrine system cause organ dysfunction and disease states. However, the cell biology of endocrine tissue ageing remains poorly understood. Here, we perform comparative 3D imaging to understand age‐related perturbations of the endothelial cell (EC) compartment in endocrine glands. Datasets of a wide range of markers highlight a decline in capillary and artery numbers, but not of perivascular cells in pancreas, testis and thyroid gland, with age in mice and humans. Further, angiogenesis and β‐cell expansion in the pancreas are coupled by a distinct age‐dependent subset of ECs. While this EC subpopulation supports pancreatic β cells, it declines during ageing concomitant with increased expression of the gap junction protein Gja1. EC‐specific ablation of Gja1 restores β‐cell expansion in the aged pancreas. These results provide a proof of concept for understanding age‐related vascular changes and imply that therapeutic targeting of blood vessels may restore aged endocrine tissue function. This comprehensive data atlas offers over > 1, 000 multicolour volumes for exploration and research in endocrinology, ageing, matrix and vascular biology. Synopsis: Despite the pathophysiological consequences of age‐dependent hormonal perturbations, endocrine organ alterations during ageing remain poorly understood. This systematic imaging atlas unveils age‐associated endocrine perturbations by characterizing endothelial cells (EC) and blood vessels in young versus old hormone‐secreting glands. High‐resolution imaging of > 60 EC and matrix markers defines the vasculature in adrenal gland, ovary, pituitary gland, testis, pancreas and thyroid gland. Capillary and artery numbers decline during ageing in mouse and human. A CD31posEmcnhighESM‐1low pancreatic islet EC subpopulation supports beta‐cell proliferation but decreases during ageing. EC‐specific ablation of age‐increased gap junction protein Gja1 rescues vessel growth in the pancreas. Abstract : Single‐cell‐resolution 3D imaging unveils organ‐based specialisation and age‐related changes in the vasculature of hormone‐secreting glands.